2006
DOI: 10.1093/occmed/kql106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of overtime work on blood pressure and body mass index in Japanese male workers

Abstract: The results of this study indicate that workers whose mean overtime was > or =50 h have lower risks of developing definite hypertension and increasing their BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 7 publications
7
31
0
4
Order By: Relevance
“…However, the results of these studies have varied considerably. Some studies reported that an increase in working hours promoted the onset of hypertension 16, 21−23) ; others reported that an increase in working hours suppressed the onset of hypertension 24,25) ; and still some other studies reported no association between the onset of hypertension and an increase in working hours 26,27) . In our present study, we found no association between the onset of hypertension and the number of hours worked.…”
Section: Working Hoursmentioning
confidence: 99%
“…However, the results of these studies have varied considerably. Some studies reported that an increase in working hours promoted the onset of hypertension 16, 21−23) ; others reported that an increase in working hours suppressed the onset of hypertension 24,25) ; and still some other studies reported no association between the onset of hypertension and an increase in working hours 26,27) . In our present study, we found no association between the onset of hypertension and the number of hours worked.…”
Section: Working Hoursmentioning
confidence: 99%
“…Most studies, except few literatures 18,19) , on the relation between work hours and obesity have been conducted in Western countries where working hours are short compared with Asian countries such as Korea. Until 2007, Korean workers had the longest working hours among countries in the Organization for Economic Cooperation and Development (OECD), and from 2008 to 2011 had the second longest working hours 20) .…”
mentioning
confidence: 99%
“…Data from more than Japanese 50,000 workers from 4 companies were evaluated. The results showing an inverse association between overtime work and prevalence of hypertension contradicted two former studies (Artazcoz et al, 2009;Yang et al, 2006), but confirmed others (Wada et al, 2006;Nakanishi et al, 2001). Despite the large database, the authors highlighted the cross-sectional design as the main study limitation that left the possibility open of residual effects of potential confounders and differences in assessments of overtime and blood pressure evaluation among the companies.…”
Section: Health and Working Timementioning
confidence: 58%